ANALISA DAN PENERAPAN ALGORITMA DES UNTUK PENGAMANAN DATA GAMBAR DAN VIDEO - Herryawan, I Putu (Jurnal Ilmu Komputer; Vol. 4, No. 2 September 2011, 2011)
System security of data and data’s secret represent one of important aspect in growth of information technology’s progress but which enough regrettably is imbalance between every growth of a technology which is not accompanied with the growth of security’s system. So that a lot of system which still be weak and have to be improved by security. Therefore data security which in character secret shall really paid to attention, to overcome the problem is hence needed an application of data security which can prevent and pacivy the data which we own from other people who have not business to acces it. One of them is method of algorithm of cryptography symmetric, because this algorithm use the same key at the conducting process of encryption and decryption, so that our data difficult to be understood and very quickly for the encryption data. Algorithm cryptography (cipher) used is DES
Keywords: Cryptohraphy, Symmetric, and Cipher